A self-healable nanocomposite based on dual-crosslinked Graphene Oxide/Polyurethane. (3rd October 2017) - Lin, Changhong; Sheng, Dekun; Liu, Xiangdong; Xu, Shaobin; Ji, Fance; Dong, Li; Zhou, Yan; Yang, Yuming
Abstract: We developed a polyurethane material has an excellent self-healing ability as well as mechanical strength. This system was achieved based on dual-crosslinked Diels-Alder (DA) covalent bonding reaction. The first cross-linking point is realized by the DA bonding of polyurethane chain. Because of grafted maleimide group, the maleimide functionalized GO (mGO) sheets can be regarded as analogous cross-linker and provide the second cross-linking point in the system. We investigated and compared the effects of as-produced GO and mGO loading and maleimide functionalization on the mechanical properties and healing efficiency of composites. As a result, compared with those of the pure polyurethane and composites filled with the GO, such maleimide functionalization is found to effectively improve the compatibility between mGO and polymer matrix, increasing mechanical properties and healing efficiency of polyurethane composites. The mechanical properties and healing efficiency of polyurethane can be tuned readily by varying mGO concentration. The healing efficiencies were up to 99% for the nanocomposite containing mGO. These results confirm maleimide functionalization improved dispersion and interfacial interaction between the fillers and the polyurethane matrix. Graphical abstract: Highlights: Synthesis of new polyurethane having pendant furan and maleimide groups (PUE, PUT). The GO was functionalized with maleimide groups. mGO act as crosslinking point to fabricate dynamic dual-crosslinked polyurethane by Diels-Alder (DA) reaction. Self-healing polyurethane could be healed highly efficiency via addition optimal mGO content.